A systematic review of immersive educational technologies in medical physics and radiation physics - Tene, Talia; Bonilla García, Nataly; Coello-Fiallos, Diana; Borja, Myrian; Vacacela Gomez, Cristian (Frontiers in Medicine, 2024)
Objective This systematic review aims to analyze and synthesize the current state of research on the role of immersive technologies, specifically augmented reality (AR), virtual reality (VR), and mixed reality (MR), in medical physics and radiation physics education. The primary focus is to evaluate their impact on learning outcomes, performance, and engagement across various educational contexts. Methods We conduct a comprehensive search of four major databases: Scopus, Web of Science, PubMed, and IEEE Xplore, covering the period from 2012 to 2023. A total of 316 articles are initially identified. After removing duplicates and screening for relevance based on titles and abstracts, 107 articles are selected for full-text review. Finally, 37 articles met the inclusion criteria and are included in the analysis. The review follows the PRISMA guidelines and utilizes the PICOS framework to structure the research question. Analysis Data extraction focuses on key variables such as the type of immersive technology used, educational context, study design, participant demographics, and measured outcomes. The studies are analyzed for their reported effects on learning outcomes, performance, and engagement. Results The review found that immersive technologies significantly enhance learning outcomes and engagement. Specifically, 36.4% of the studies reported increased engagement, while 63.6% of studies focusing on practical skills noted performance improvements. The use of AR, VR, and MR showed broad applicability across different educational levels, from undergraduate courses to professional training programs. Conclusion Immersive technologies have considerable potential to transform medical and radiation physics. They enhance student engagement, improve learning outcomes, and boost performance in practical skills. Nevertheless, future research should focus on standardizing methodologies, expanding participant demographics, and exploring long-term impacts on skill retention and clinical practice. This review provides a valuable resource for guiding future research and implementing innovative educational strategies in the dynamic fields of medical physics and radiation physics.